2017
DOI: 10.1002/slct.201702854
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Sonogashira Reaction in Water

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…The current mechanistic understanding concerning copper(II) catalytic systems involves reduction of copper(II) to copper(I) by the solvent or the ligand (usually amines), followed by the mechanism proposed for copper(I) systems . The transient formation of yellow solids in the reaction mixture of copper‐catalyzed Sonogashira couplings has been attributed to intermediate copper acetylides . In the course of our experiments we observed that the reaction mixtures very often turned yellow, during the first minutes of the reaction, a fact we also believe is due to the transient formation of copper acetylides.…”
Section: Resultssupporting
confidence: 56%
“…The current mechanistic understanding concerning copper(II) catalytic systems involves reduction of copper(II) to copper(I) by the solvent or the ligand (usually amines), followed by the mechanism proposed for copper(I) systems . The transient formation of yellow solids in the reaction mixture of copper‐catalyzed Sonogashira couplings has been attributed to intermediate copper acetylides . In the course of our experiments we observed that the reaction mixtures very often turned yellow, during the first minutes of the reaction, a fact we also believe is due to the transient formation of copper acetylides.…”
Section: Resultssupporting
confidence: 56%
“…Based on the abovementioned observations, we suggested the most possible mechanistic pathway for this method. According to the results obtained from the control experiments as well as the literature, [10][11][12]37 under the same reaction conditions. No coupling products were found in the mixture.…”
Section: Mechanistic Studymentioning
confidence: 91%
“…However, these methods often require expensive Pd catalysts and Cu salts as cocatalyst with excessive ligands/amines or harsh thermal conditions. Recently, a number of reports have demonstrated different modifications in a catalytic fashion, such as a) Cu‐free Pd‐catalytic systems, b) Pd‐free Fe‐, Ni‐, or Cu‐complexes, and c) Cu‐catalysts with ligands under harsh conditions . Among them, Pd‐free copper‐catalyzed Sonogashira cross‐couplings are the predominant inexpensive protocols for constructing conjugated alkynes, However, the usage of excess ligands and the harsh thermal reaction conditions diminish their merits.…”
Section: Methodsmentioning
confidence: 99%